Verbal communication used by cardiologist at National Heart Centre Malaysia - Govindaraju, Vimala; Omar, Siti Zobidah (Human Resource Management Academic Research Society, 2017)
Issues regarding the relationship between doctors and patients have been discussed generally. Literature concerning the health care was based on the performance and patients’ view on the facility provided in the health care services. However, some issues identified on verbal communication used by the cardiologist in their daily career life. The objective of this paper is to focus on the verbal communication used by the cardiologists with their patients. This study uses qualitative methods and a phenomenological approach. A total of 15 cardiologists were interviewed. An in-depth interview and observation were used to study the verbal communication skills used by cardiologists in the National Heart Institute, Kuala Lumpur Malaysia. The researcher then transcribed the data verbatim and analysed it using ATLAS.ti7 software a allow coding the key themes, sub-themes, and interrelationships. The results of the study show that the verbal communication skills which are greeting and welcoming the patients; use the preferred language during the consultation session that will easily understand by the patients; give clear, supportive, and encouraging health care information in order to build good relationship with patients. Based on the results gained, it is recommended that doctor can be given training in improving and maintain verbal communication skills during the interactive session with their patients.